Enhancing Bioactive Cordycepin Production via Precision Fermentation with an Engineered Aspergillus oryzae - Jutamas Anantayanon; Warinthon Chamkhuy; Nakul Rattanaphan; Sarocha Panchanawaporn; Kobkul Laoteng; Sukanya Jeennor (Fermentation)
An optimal culture medium and highly stable biometabolites are important in industrial production processes. The response surface methodology with a Box–Behnken design was performed to determine the optimal culture medium of an engineered Aspergillus oryzae strain for cordycepin production by submerged fermentation. The influences of glucose, yeast extract, and adenine concentrations on cordycepin production were explored, and their concentrations were used for experimental design. The results reveal that the optimal culture components involved 30.0 g/L of glucose, 9.8 g/L of yeast extract, and 1.5 g/L of adenine. As predicted, the maximum cordycepin concentration (1724.53 ± 18.30 mg/L) was obtained with a short fermentation time (2 days). A significant increase in cordycepin yield (>50% increase) was observed in the culture grown in the optimized culture medium compared to that grown in the basal medium. A xanthine oxidase inhibitory activity assay demonstrated that the cordycepin product had a pharmacological function. It exhibited strong stability under high thermal and acidic conditions, with over 95% product recovery. The findings of this study are valuable for developing cost-effective processes for producing health-benefiting products.